2023
DOI: 10.1002/app.54552
|View full text |Cite
|
Sign up to set email alerts
|

Terpolymers of acrylonitrile, methyl acrylate, and 2‐acrylamido‐2‐methylpropane sulfonic acid for carbon fiber precursor: Effect of comonomers on the thermal stabilization of polyacrylonitrile copolymers

Qiufei Chen,
Bin He,
Yatian Chen
et al.

Abstract: Polyacrylonitrile (PAN) copolymers are important precursors for the preparation of high‐performance PAN‐based carbon fibers. In this study, different ratios of P(AN‐co‐AMPS) and P(AN‐co‐MA‐co‐AMPS) were prepared by solution polymerization. The compositional structure, thermal, and crystallization properties of P(AN‐co‐AMPS) and P(AN‐co‐MA‐co‐AMPS) were characterized. The results show that an increase in the AMPS feeding ratio is beneficial for improving the thermal stability and crystallization ability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Carbon fiber, due to its excellent characteristics of lightweight and high strength, is widely used in lightweight composite materials and plays an irreplaceable role in the fields of national defense, military industry, aerospace, and sports equipment. Carbon fiber is prepared through thermal stabilization and carbonization of precursor fibers, , with over 90% of commercial carbon fibers still using polyacrylonitrile (PAN) as the precursor material, although many studies have attempted to use other polymers with linear or cyclic structures to prepare carbon fibers. Numerous researchers have also been exploring the structure–property relationships of carbon fibers in an attempt to develop high-performance carbon fibers that are increasingly close to theoretical strength and modulus. , Li et al found that the microcrystal size increased with the increase in fiber strength; the size of the micropore also increased, but its quantity decreased . Hao et al analyzed the effect of the microcrystal structure and preferred orientation of different grades of commercial carbon fibers on tensile modulus and found that the tensile modulus of carbon fiber decreased gradually with increasing interlayer spacing and orientation angle, while it rose with the increase of microcrystal size.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber, due to its excellent characteristics of lightweight and high strength, is widely used in lightweight composite materials and plays an irreplaceable role in the fields of national defense, military industry, aerospace, and sports equipment. Carbon fiber is prepared through thermal stabilization and carbonization of precursor fibers, , with over 90% of commercial carbon fibers still using polyacrylonitrile (PAN) as the precursor material, although many studies have attempted to use other polymers with linear or cyclic structures to prepare carbon fibers. Numerous researchers have also been exploring the structure–property relationships of carbon fibers in an attempt to develop high-performance carbon fibers that are increasingly close to theoretical strength and modulus. , Li et al found that the microcrystal size increased with the increase in fiber strength; the size of the micropore also increased, but its quantity decreased . Hao et al analyzed the effect of the microcrystal structure and preferred orientation of different grades of commercial carbon fibers on tensile modulus and found that the tensile modulus of carbon fiber decreased gradually with increasing interlayer spacing and orientation angle, while it rose with the increase of microcrystal size.…”
Section: Introductionmentioning
confidence: 99%